Influence of protein intake and training status on nitrogen balance and lean body mass - Tarnopolsky, M. A.; MacDougall, J. D.; Atkinson, S. A. (Journal of Applied Physiology, 1988)
The present study examined the effects of training status (endurance exercise or body building) on nitrogen balance, body composition, and urea excretion during periods of habitual and altered protein intakes. Experiments were performed on six elite bodybuilders, six elite endurance athletes, and six sedentary controls during a 10-day period of normal protein intake followed by a 10-day period of altered protein intake. The nitrogen balance data revealed that bodybuilders required 1.12 times and endurance athletes required 1.67 times more daily protein than sedentary controls. Lean body mass (density) was maintained in bodybuilders consuming 1.05 g protein.kg-1.day-1. Endurance athletes excreted more total daily urea than either bodybuilders or controls. We conclude that bodybuilders during habitual training require a daily protein intake only slightly greater than that for sedentary individuals in the maintenance of lean body mass and that endurance athletes require daily protein intakes greater than either bodybuilders or sedentary individuals to meet the needs of protein catabolism during exercise.